[Current value of magnetic resonance imaging for diagnosis of coronary heart disease] - Wiesmann, F; Taylor, A; Neubauer, S; Pennell, D (1997)
Magnetic Resonance Imaging (MRI) is a non-invasive imaging technique with increasing importance in clinical medicine. It has become a valuable and reliable imaging tool in the diagnosis and management of many medical and surgical conditions. Important advantages of MRI are its flexibility in orientation of imaging plane and the possibility of both anatomical and functional imaging. MRI is based on the application and detection of radio signals and works without any exposure to ionizing radiation, and therefore it is regarded as a safe imaging technique. In the heart there are well established imaging indications such as in acquired and congenital heart disease, pericardial and aortic disease and visualisation of cardiac masses and hypertrophy. Its applications in coronary artery disease (CAD) have been relatively limited, but recent developments in ultrafast imaging sequences and computer hardware have led to a considerable improvement in spatial and temporal image resolution. This has made applications in CAD a possibility, particularly coronary imaging and myocardial perfusion imaging. Recent clinical studies report good correlation between Magnetic Resonance Coronary Angiography (MRCA) and conventional x-ray contrast angiography in the detection of coronary lesions. In the assessment of coronary artery bypass graft (CABG) patency and the definition of anomalous coronary arteries, MRI showed good sensitivity and specificity. The first results of coronary artery flow measurements have now been reported. Myocardial perfusion imaging and stress-ventriculography for detection of wall motion abnormalities are reported as indirect imaging methods with high reliability and clinical value in the diagnosis of CAD. This overview describes recent developments in cardiac MRI and assesses the current and future value of MRI for clinical cardiology.